2021 IEEE 93rd Vehicular Technology Conference (VTC2021-Spring) 2021
DOI: 10.1109/vtc2021-spring51267.2021.9449034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of LTE-V2X Connectivity on Global Occupancy Maps in a Cooperative Collision Avoidance (CoCA) System

Abstract: Cooperative Intelligent Transport Systems (C-ITS) are expected to fulfill the needs of various emerging road safety applications. In this work, we focus on improving C-ITS vulnerable road users safety by considering a Cooperative Collision Avoidance (CoCA) system. In this system, vehicles rely on onboard sensors in order to generate local occupancy maps that are transmitted by means of LTE-V2X connectivity to a fusion center. The latter executes the fusion of successfully received local maps, in order to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The RSUs fused all the messages into a global occupancy map and sent it back to all vehicles in range. The authors found that the configuration for the best performance was a message size of 1,685 bytes for global occupancy maps, which led to the lowest obstacle mis-detection rate and a packet generation rate of 10 Hz when the number of vehicles was less than 70 and 5 Hz otherwise [71].…”
Section: Author -Institutementioning
confidence: 99%
“…The RSUs fused all the messages into a global occupancy map and sent it back to all vehicles in range. The authors found that the configuration for the best performance was a message size of 1,685 bytes for global occupancy maps, which led to the lowest obstacle mis-detection rate and a packet generation rate of 10 Hz when the number of vehicles was less than 70 and 5 Hz otherwise [71].…”
Section: Author -Institutementioning
confidence: 99%
“…The tracking quality of locally perceived objects will not be improved by the perception data from other ITS-Ss, which would otherwise be achieved in joint fusion schemes. There are also occupancy-grid based data fusion methods for CP, such as in [6], [7]. This kind of fusion framework is considered computationally expensive, where pixel-wise iterative fusion is required.…”
Section: Introductionmentioning
confidence: 99%
“…For each vehicle, occupancy grids are calculated from sensor measurements and then merged in terms of occupancy and confidence. In [9], authors evaluate the impact of LTE-V2X connectivity performance on the fusion of local occupancy maps. Moreover, a study was conducted in order to define the best compromises between the physical layer configuration, occupancy maps resolution, message periodicity, and obstacle detection capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…None of these papers have considered a fusion algorithm that can analyze received CPMs according to the standardized generation rules. The occupancy maps impose the use of large packets and thus high Modulation Code Schemes (MCS) [9], which may affect the connectivity performance. Besides, the fusion of local occupancy maps proposed in [8] may induce computation complexity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation